Stress work effect on natural convection flow along a vertical flat plate with Joule heating and heat conduction - Alam, Md M; Alim, MA; Chowdhury, Md. MK (Journal of Mechanical Engineering, 2008)
In the present paper, the effects of viscous dissipation and pressure stress work on free convection flow along a vertical plate have been investigated. Joule heating and heat conduction through a wall of finite thickness are considered in the investigation. With a goal to attain similarity solutions of the problem, the developed equations are made dimensionless by using suitable transformations. The non-dimensional equations are then transformed into non-similar forms by introducing non- similarity transformations. The resulting non-similar equations together with their corresponding boundary conditions based on conduction and convection are solved numerically by using the finite difference method along with Newton's linearization approximation. Numerically calculated velocity profiles, temperature profiles, skin friction coefficient and the surface temperature distributions are shown both on graphs and tables for different values of the parameters entering into the problem. Keywords: Free convection, Joule heating, viscous dissipation and pressure work. DOI: 10.3329/jme.v38i0.896 Journal of Mechanical Engineering Vol.38 Dec. 2007 pp.18-24